Chlamydia pecorum infections in sheep and cattle: A common and under-recognised infectious disease with significant impact on animal health. Issue 3 (December 2015) - Walker, Evelyn; Lee, Effie J.; Timms, Peter; Polkinghorne, Adam
Highlights: Chlamydia pecorum is a common but under-recognised cause of disease in livestock. Joint and central nervous system infections are the most economically significant. Sub-clinical infections may also have major impacts on on-farm productivity. Different strains are associated with disease versus asymptomatic colonisation. Chlamydia serology lacks sensitivity and is difficult to interpret by clinicians. Abstract: There is a growing recognition that infections of livestock by the obligate intracellular bacterium, Chlamydia pecorum, are more widespread than was previously thought. A range of diseases have been associated with this pathogen, with the most important manifestations including infectious arthritis, infertility, enteritis, reduced growth rates, mastitis, and pneumonia. C. pecorum infections have also been associated with sub-clinical disease, highlighting our lack of knowledge about its true economic impact on livestock producers. Diagnosis of C. pecorum infection is based on clinical findings, serology and histopathology, which are not necessarily implemented in subclinical or early stages of infection, thus potentially contributing to under-diagnosis and under-reporting of infections associated with this bacterium. Recent molecular epidemiology studies have revealed that C. pecorum is genetically diverse and that there may be an association between certain strains and disease in sheep and cattle. Antimicrobial treatment of affected animals has questionable efficacy, justifying development of chlamydia vaccines for livestock. This review summarises current knowledge of the prevalence and impact of C. pecorum infections in sheep and cattle and provides an update on attempts to improve detection, management and treatment of infections by this important obligate intracellular pathogen.